Unusually Strong Temperature Dependence of P2X3 Receptor Traffic to the Plasma Membrane - Pryazhnikov, Evgeny; Fayuk, Dmitriy; Niittykoski, Minna; Giniatullin, Rashid; Khiroug, Leonard (Frontiers in Cellular Neuroscience, 2011)
ATP-gated P2X3 receptors are expressed by nociceptive neurons and participate in transduction of pain. Responsiveness of P2X3 receptors is strongly enhanced at high temperatures, suggesting a role for these receptors in temperature detection. Since sustained responsiveness depends on receptor trafficking to the plasma membrane, we employed total-internal reflection fluorescence (TIRF) microscopy to highlight perimembrane pool of DsRed-tagged P2X3 receptors and studied the effects of temperature on perimembrane turnover of P2X3-DsRed. Patch clamp recordings confirmed membrane expression of functional, rapidly desensitizing P2X3-DsRed receptors. By combining TIRF microscopy with the technique of fluorescence recovery after photobleaching (FRAP), we measured the rate of perimembrane turnover of P2X3-DsRed receptors expressed in hippocampal neurons. At room temperature, the P2X3-DsRed perimembrane turnover as measured by TIRF-FRAP had a time constant of ~2 min. At 29oC, receptor turnover was strongly accelerated, yielding an extremely high temperature dependence coefficient Q10 ~4.5. In comparison, AMPA receptor turnover measured with TIRF-FRAP was only moderately sensitive to temperature (Q10 ~1.5). The traffic inhibitor Brefeldin A selectively decelerated P2X3-DsRed receptor turnover at 29oC, but had no effect at 21oC (Q10 ~1.5). This indicates that receptor traffic to plasma membrane, rather than endosomal recycling, is the key temperature-sensitive component of P2X3 turnover. The selective inhibitor of the RhoA kinase Y27632 significantly decreased the temperature dependence of P2X3-DsRed receptor turnover (Q10 ~2.0). In summary, the RhoA kinase-dependent membrane trafficking of P2X3 receptors to plasma membrane has an exceptional sensitivity to temperature. These data link two fundamental sensory processes, thermoreception and nociception, which are likely co-involved in hyperthermia-associated pain states.